Analysis of Factors Affecting Pregnant Women's Compliance With Iron Supplementation (Fe Tablets) at Anggalomoare Health Center, Konawe Regency - Indah Indah; Ruslan Majid; Asriati Asriati (Faculty of Medicine, Universitas Tadulako, 2026)
Background: Low adherence to iron (Fe) tablet supplementation among pregnant women remains a major barrier to preventing maternal anemia and its associated adverse pregnancy outcomes. Objective: This study aimed to analyze the factors influencing pregnant women’s adherence to Fe tablet consumption, with particular emphasis on antenatal care (ANC) visits and husband’s support. Methods: An analytical observational study with a cross-sectional design was conducted among 96 pregnant women attending the Anggalomoare Public Health Center who met the inclusion criteria. Data were collected using a validated questionnaire and analyzed through descriptive statistics, Chi-square tests, and multiple logistic regression to identify factors associated with adherence to Fe tablet consumption. Results: Knowledge (p<0.001), attitude (p<0.001), husband’s support (p<0.001), and ANC visits (p=0.007) were significantly associated with adherence to Fe tablet consumption, whereas satisfaction with healthcare services was not significantly associated (p=0.074). Multivariable analysis identified maternal attitude as the strongest predictor of adherence, followed by husband’s support and maternal knowledge. Conclusion: Improving pregnant women’s adherence to Fe tablet supplementation requires strengthening positive maternal attitudes, increasing husband’s involvement, and enhancing maternal knowledge through quality ANC services and family-centered health education, thereby supporting better maternal and fetal health outcomes and reducing the risk of pregnancy-related anemia.